(untitled) (Proceeding of SINERGY, 2026)
Innovation has long been recognized as a primary driver of organizational transformation, yet traditional frameworks often overlook the social and cultural dimensions inherent in this process. This study examines how youth involvement in Indonesian start-up companies contributes to organizational transformation through a multiparadigm innovation lens that integrates economic, social, and cultural dimensions. Using a qualitative, document-based research design, the study analyzes a diverse range of Indonesian start-ups—including prominent examples such as Gojek, Tokopedia, Bukalapak, and Ruangguru—to trace how youth agency reshapes organizational practices and value creation. The findings reveal that economic innovation in these start-ups is characterized by digital platformization and scalable business models that prioritize market inclusivity and the integration of micro-entrepreneurs. Socially, innovation is embedded within the core operational logic, positioning start-ups as agents of collective value creation and social problem-solving, particularly in sectors such as education and environmental sustainability. Culturally, the study highlights how localization strategies and the alignment of services with local norms and values act as strategic resources to enhance organizational legitimacy and user trust. Synthesizing these dimensions, the research demonstrates that youth-driven innovation in Indonesia operates as an integrated system where economic viability, social responsibility, and cultural embeddedness are mutually reinforcing. This study contributes to the literature by extending multiparadigm innovation theory into the context of an emerging economy, providing empirical evidence of how young actors navigate and reconcile global innovation logics with local institutional environments. The results offer practical implications for policymakers and practitioners seeking to foster a sustainable start-up ecosystem that balances commercial growth with broader societal and cultural impact.